Assessment of Nanosecond Laser Ablation Multi‐Collector Inductively Coupled Plasma‐Mass Spectrometry for Pb and Sr Isotopic Determination in Archaeological Glass: Mass Bias Correction Strategies and Results for Corning Glass Reference Materials. Issue 2 (15th January 2018) - Van Ham‐Meert, Alicia; Chernonozhkin, Stepan M.; Van Malderen, Stijn J.M.; Van Acker, Thibaut; Vanhaecke, Frank; Degryse, Patrick
Abstract : This work presents an evaluation of various methods for in situ high‐precision Sr and Pb isotopic determination in archaeological glass (containing 100–500 μg g −1 target element) by nanosecond laser ablation multi‐collector‐inductively coupled plasma‐mass spectrometry (ns‐LA‐MC‐ICP‐MS). A set of four soda‐lime silicate glasses, Corning A–D, mimicking the composition of archaeological glass and produced by the Corning Museum of Glass (Corning, New York, USA), were investigated as candidates for matrix‐matched reference materials for use in the analysis of archaeological glass. Common geological reference materials with known isotopic compositions (USGS basalt glasses BHVO‐2G, GSE‐1G and NKT‐1G, soda‐lime silicate glass NIST SRM 610 and several archaeological glass samples with known Sr isotopic composition) were used to evaluate the ns‐LA‐MC‐ICP‐MS analytical procedures. When available, ns‐LA‐MC‐ICP‐MS results for the Corning glasses are reported. These were found to be in good agreement with results obtained via pneumatic nebulisation ( pn ) MC‐ICP‐MS after digestion of the glass matrix and target element isolation. The presence of potential spectral interference from doubly charged rare earth element (REE) ions affecting Sr isotopic determination was investigated by admixing Er and Yb aerosols by means of pneumatic nebulisation into the gas flow from the laser ablation system. It was shown that doubly charged REE ions affect the Sr isotope ratios, but that this could be circumvented by operating the instrument at higher mass resolution. Multiple strategies to correct for instrumental mass discrimination in ns‐LA‐MC‐ICP‐MS and the effects of relevant interferences were evaluated. Application of common glass reference materials with basaltic matrices for correction of ns‐LA‐MC‐ICP‐MS isotope data of archaeological glasses results in inaccurate Pb isotope ratios, rendering application of matrix‐matched reference materials indispensable. Correction for instrumental mass discrimination using the exponential law, with the application of Tl as an internal isotopic standard element introduced by pneumatic nebulisation and Corning D as bracketing isotopic calibrator, provided the most accurate results for Pb isotope ratio measurements in archaeological glass. Mass bias correction relying on the power law, combined with intra‐element internal correction, assuming a constant 88 Sr/ 86 Sr ratio, yielded the most accurate results for 87 Sr/ 86 Sr determination in archaeological glasses Key Points: Sr and Pb isotopic composition of Corning glass materials by pn ‐MC‐ICP‐MS Accurate ns‐LA‐MC‐ICP‐MS determination of Sr isotopic composition of archaeological glass when corrected using the power law. ns‐LA‐MC‐ICP‐MS determination of Pb isotopic composition of archaeological glass is possible with matrix‐matched RMs using Tl and the modified Russell's law.